Developing a strategy for computational lab skills training through Software and Data Carpentry: Experiences from the ELIXIR Pilot action - Pawlik, A; van Gelder, C; Nenadic, A; Palagi, P; Korpelainen, E; Lijnzaad, P; Marek, D; Sansone, S; Hancock, J; Goble, C (F1000Research, 2017)
Quality training in computational skills for life scientists is essential to allow them to deliver robust, reproducible and cutting-edge research. A pan-European bioinformatics programme, ELIXIR, has adopted a well-established and progressive programme of computational lab and data skills training from Software and Data Carpentry, aimed at increasing the number of skilled life scientists and building a sustainable training community in this field. This article describes the Pilot action, which introduced the Carpentry training model to the ELIXIR community.